2020
DOI: 10.3390/inorganics8050031
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Derivatives of Molecular Tin Compounds. Part 1: Hemicarbonato and Carbonato Complexes

Abstract: This review focuses on organotin compounds bearing hemicarbonate and carbonate ligands, and whose molecular structures have been previously resolved by single-crystal X-ray diffraction analysis. Most of them were isolated within the framework of studies devoted to the reactivity of tin precursors with carbon dioxide at atmospheric or elevated pressure. Alternatively, and essentially for the preparation of some carbonato derivatives, inorganic carbonate salts such as K2CO3, Cs2CO3, Na2CO3 and NaHCO3 were also u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…The carbamate moiety is terminally O-bonded to Sn [Sn−O = 2.1346(16) Å] and its orientation can be viewed almost perpendicular to the NCCCN plane of the β-diketiminate ligand ( Figure 5). This mode of coordination is unusual for carbamates and is similar to that observed in the case of hemicarbonato derivatives [1]. The X-ray structure of complex 7 has not been reported but the spectroscopic data are very similar to 6 ( Table 2) and the authors mention that for both compounds, the insertion reaction is irreversible, even under reduced pressure.…”
Section: X-ray Crystal Structuressupporting
confidence: 75%
See 4 more Smart Citations
“…The carbamate moiety is terminally O-bonded to Sn [Sn−O = 2.1346(16) Å] and its orientation can be viewed almost perpendicular to the NCCCN plane of the β-diketiminate ligand ( Figure 5). This mode of coordination is unusual for carbamates and is similar to that observed in the case of hemicarbonato derivatives [1]. The X-ray structure of complex 7 has not been reported but the spectroscopic data are very similar to 6 ( Table 2) and the authors mention that for both compounds, the insertion reaction is irreversible, even under reduced pressure.…”
Section: X-ray Crystal Structuressupporting
confidence: 75%
“…N,N -diphenylurea is formed as byproduct (4%). From a mechanistic point of view, the hemicarbonato tin complex, n-Bu 2 Sn(OMe)(OCO 2 Me), resulting from the reactivity of CO 2 with n-Bu 2 Sn(OMe) 2 [1,31], is claimed as the key intermediate of the reaction. In the case of reactions involving n-Bu 2 Sn(OBu-n) 2 , the authors also showed that the starting tin complex could be regenerated after the first catalytic run (by reacting with n-BuOH) and could thus be recycled without loss of activity.…”
Section: Tin-promoted Insertion Reaction Of Co 2 Into C-n Bondsmentioning
confidence: 99%
See 3 more Smart Citations